Prevalence and Risk Factors of Cervical Inflammations Among Low-Income Women in Rasht, Iran - Seyedeh Hajar Sharemi; Faezeh Fashkhami; Tayebeh Omid Khah; Fariborz Mansour Ghanaei; Niloofar Faraji; Tahereh Zeinali; Sara Yeganeh; Farahnz Joukar (Disease and Diagnosis)
Background: Cervical inflammations are among one of the most genital-related complications. This study aimed to investigate the prevalence of cervical inflammations and identify associated risk factors among low-income women in Rasht, Iran. Materials and Methods: This cross-sectional study was conducted on 300 low-income women who referred to Alzahra Hospital, Rasht, Iran. Demographical and clinical data were collected from patients’ archived medical records. Pap smear tests were performed using the liquid-based method to evaluate cervical lesions, and all data were analyzed using SPSS-19 based on a significant level<0.05. Results: The mean age of participants was 46.6±7.43 years. Cervical inflammation was detected in 94.3% of participants, and 1% showed precancerous lesions. Most patients had mild inflammation (42.7%). Overall, 3, 21, and 21 patients had trichomonas infection, bacterial infection, and candida infection, respectively. The existence of cervical inflammations was significantly higher in patients with a body mass index of 25–30 kg/m2 (P<0.05). Family history of cancers demonstrated no significant association with cervical inflammation (P>0.05), while age at first menstruation and age of first delivery were significant risk factors for cervical inflammation (P<0.05). Conclusion: According to the results, while the frequency of precancerous lesions was low, the prevalence of inflammation was high among participants. Therefore, early detection and intervention by screening tests such as Pap smear are essential to the pre-diagnosis of cervical cancer (CC).